2023
DOI: 10.1177/15459683231159660
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation Initiated Early in Post-Stroke Recovery: A Feasibility Study

Abstract: Background Enhanced neural plasticity early after stroke suggests the potential to improve outcomes with intensive rehabilitation therapy. Most patients do not get such therapy, however, due to limited access, changing rehabilitation therapy settings, low therapy doses, and poor compliance. Objective To examine the feasibility, safety, and potential efficacy of an established telerehabilitation (TR) program after stroke initiated during admission to an inpatient rehabilitation facility (IRF) and completed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Substantial improvement was reported in all motor outcome measures. This improvement was larger in comparison to other reported recovery measures 13,14,41 . A new study showed that adding 30 hours of upper extremity training resulted in better motor improvement than standard of care alone 16 .…”
Section: The Motor Benefits Of the Interventioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Substantial improvement was reported in all motor outcome measures. This improvement was larger in comparison to other reported recovery measures 13,14,41 . A new study showed that adding 30 hours of upper extremity training resulted in better motor improvement than standard of care alone 16 .…”
Section: The Motor Benefits Of the Interventioncontrasting
confidence: 62%
“…Another suggested avenue is to expand this protocol in time and to include a telerehabilitation component. Although this type of rehabilitation is relatively new, it has been shown to be feasible 41 . Therefore, we suggest further studies regarding the implementation of high dosage and intensity with a such a component.…”
Section: Implementation Recommendationsmentioning
confidence: 99%
“…The majority (86/103, 83%) [ 47 - 51 , 53 - 56 , 58 , 59 , 61 , 63 - 68 , 71 - 86 , 89 - 95 , 97 - 105 , 107 , 109 , 111 , 112 , 114 , 115 , 117 - 126 , 128 - 136 , 138 - 148 ] were published in the past 10 years. Most studies took place in North America (41/103, 40%) [ 46 - 49 , 52 , 55 , 56 , 60 , 64 - 67 , 69 , 70 , 72 , 74 , 76 - 78 , 80 , 85 - 88 , 92 , 93 , 97 , 99 , 101 , 108 - 110 , 126 - 129 , 137 , 138 , 141 , 142 , 145 ] and Europe (35/103, 34%) [ 51 , 53 , 54 , 57 , 58 , 62 , 63 , 68 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Most studies took place in North America (41/103, 40%) [ 46 - 49 , 52 , 55 , 56 , 60 , 64 - 67 , 69 , 70 , 72 , 74 , 76 - 78 , 80 , 85 - 88 , 92 , 93 , 97 , 99 , 101 , 108 - 110 , 126 - 129 , 137 , 138 , 141 , 142 , 145 ] and Europe (35/103, 34%) [ 51 , 53 , 54 , 57 , 58 , 62 , 63 , 68 , 71 , 79 , 81 - 84 , 89 , 111 , 113 - 125 , 132 , 136 , 140 , 143 , 146 , 147 ], with the remainder in Asia (16/103, 16%) [ 50 , 59 , 61 , 91 , 94 , 95 , 98 , 100 , 102 - 104 , 107 , 135 , 139 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation